WHEN SILENCE SPEAKS: PRAGMATIC ROLES OF PAUSES AND HESITATIONS IN POLITICAL DISCOURSE (ENGLISH AND UZBEK PERSPECTIVES) - Samatullayev , Dilshod (Scientific practical conference, 2025)
Following the general tradition of political discourse studies, this article explores the extralinguistic dimension of silence and hesitation in English and Uzbek political discourse. It examines their pragmatic roles, showing how pauses and hesitations may appear spontaneously or be used strategically in the way of turning silence from a gap in speech into a powerful rhetorical voice in political communication. The study demonstrates silence as a deliberate resource of persuasion within political rhetoric.